The More‐than‐human Geographies of Field Science. Issue 8 (2nd August 2013) - Forsyth, Isla
Abstract: Geographers have increasingly begun to attend to the local environments of science, considering how these spaces shape and influence knowledge production. This paper will explore the insights a spatial analytic can contribute to the history of science by exploring one scientific performance space; the field site. Already, rich and insightful studies into the geographies of field science have figured these sites as complex, subjective and lively places. However, so far, there appears to have only been peripheral attention paid to the multiple and myriad nonhuman animals that are present in the field. The field is a site where animals have been the object of study, provided transport, companionship, sport and food, but their presence within the history of field science is conspicuously absent. This paper asks how to study the spatialities of animal lives enrolled in the diverse technologies and knowledge that encompass scientific practice, and considers what such an engagement could offer to contemporary scientific study. Therefore, this paper will review animal and hybrid geographies, and methodological tools that attend to the performativity of science, such as the actor–network theory and Pickering's 'the mangle'. It will consider what these literatures and conceptual frameworks can add to understandings of the historical, social, cultural and political nature of more‐than‐human knowledge through a consideration of field science.